Litter production in a Quercus suber forest of Montseny (NE Spain) and its relationship to meteorological conditions (Ann. For. Sci., 2006)
From 1996 to 2002 the monthly litterfall in a Quercus suber forest ecosystem of Montseny (NE Spain) was recorded and its relationship to meteorological variables was statistically analysed. The average annual production (477 g m-2 yr-1) was similar to those found in other Mediterranean evergreen forests with relatively high rainfall. The main components were the leaves (55% of the total biomass), followed by acorns (22%) and twigs (16%). Litter production was highest during May and June, when the majority of the old leaves fell. When the meteorological conditions were favourable, a second leaf fall collection was observed. Acorn production in 2001 was about nine times that of the previous years, indicating a mast year. In general, the different litterfall components were highly correlated in time except for the acorns. Interannual covariation was significant for leaves/twigs and leaves/catkins. Catkins were the most variable component with also strong seasonality, acorns were also very variable with low seasonality, while leaves were less variable and with the strongest seasonality. After accounting for seasonal covariation, there were significant effects of rainfall on twig litterfall and of temperature on leaf litterfall, the years with highest leaf litterfall being the hottest.